Effects of Hospital and Surgeon Volume on Patient Outcomes After Total Joint Arthroplasty: Reported From the American Joint Replacement Registry. Issue 11 (1st June 2022) - Siddiqi, Ahmed; Alamanda, Vignesh K.; Barrington, John W.; Chen, Antonia F.; De, Ayushmita; Huddleston, James I.; Bozic, Kevin J.; Lewallen, David; Piuzzi, Nicolas S.; Mullen, Kyle; Porter, Kimberly R.; Springer, Bryan D.
Abstract : Background: The purpose of this study was to evaluate outcomes and complications because it relates to surgeon and hospital volume for patients undergoing primary total hip arthroplasty (THA) and total knee arthroplasty (TKA) using the American Joint Replacement Registry from 2012 to 2017. Methods: A retrospective study was conducted on Medicare-eligible cases of primary elective THAs and TKAs reported to the American Joint Replacement Registry database and was linked with the available Centers of Medicaid and Medicare Services claims and the National Death Index data from 2012 to 2017. Surgeon and hospital volume were defined separately based on the median annual number of anatomic-specific total arthroplasty procedures performed on patients of any age per surgeon and per hospital. Values were aggregated into separate surgeon and hospital volume tertile groupings and combined to create pairwise comparison surgeon/hospital volume groupings for hip and knee. Results: Adjusted multivariable logistic regression analysis found low surgeon/low hospital volume to have the greatest association with all-cause revisions after THA (odds ratio [OR], 1.63, 95% confidence interval [CI], 1.41-1.89, P < 0.0001) and TKA (OR, 1.72, 95% CI, 1.44-2.06, P < 0.0001), early revisions because of periprosthetic joint infection after THA (OR, 2.50, 95% CI, 1.53-3.15, P < 0.0001) and TKA (OR, 2.18, 95% CI, 1.64-2.89, P < 0.0001), risk of early THA instability and dislocation (OR, 2.47, 95% CI, 1.77-3.46, P < 0.0001), and 90-day mortality after THA (OR, 1.72, 95% CI, 1.27-2.35, P = 0.0005) and TKA (OR, 1.47, 95% CI, 1.15-1.86, P = 0.002). Conclusion: Our findings demonstrate considerably greater THA and TKA complications when performed at low-volume hospitals by low-volume surgeons. Given the data from previous literature including this study, a continued push through healthcare policies and healthcare systems is warranted to direct THA and TKA procedures to high-volume centers by high-volume surgeons because of the evident decrease in complications and considerable costs associated with all-cause revisions, periprosthetic joint infection, instability, and 90-day mortality. Level of Evidence: III